Hubungan Proses Pelayanan Dokumen dan Clearance Kapal Tug Boat dengan Kualitas Operasional Keagenan di PT. Adira Shipping Management Banjarmasin - Isnain Rizal Nur Fauzan1; M Aji Luhur Pambudi; Kumila Hanik (JURNAL TRANSMA, 2025)
This research was conducted to understand how the process of document service and tug boat clearance affects the operational quality of the agency at PT. Adira Shipping Management Banjarmasin. In agency operational activities, document service and vessel clearance are crucial tasks that must be carried out quickly and accurately to support the smooth operation of vessels in the port. This research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The method used in this research is qualitative descriptive method, which aims to provide an in-depth overview of the objects being studied based on data obtained from observations, interviews, and documentation. Data analysis techniques are conducted through data triangulation, which involves comparing and confirming data from various sources to enhance the validity and accuracy of the research results. The research results indicate that the quality of the document service process and ship clearance carried out by PT. Adira Shipping Management is already quite good, but there are still obstacles such as delays in administrative processes and coordination between agencies. The document service and ship clearance processes have been carried out according to procedures, but there are still some technical issues that affect operational efficiency. These findings are expected to serve as materials for evaluation and improvement in enhancing the quality of agency services in the future.